Developing Modern Livestock Production in Tropical Countries Proceedings of the 5th Animal Production International Seminar (APIS 2022), Malang, Indonesia, 10 November 2022 - Adli, Danung Nur; Pramujo, Muhammad; Yekti, Aulia Puspita Anugra (Taylor & Francis, 2023)
The Animal Production International Seminar (APIS) is the first international conference held by the Faculty of Animal Science, Universitas Brawijaya. APIS was held for the first time in 2010 and was repeated every three years. In 2022, the 5th APIS was organized as an online meeting. The Faculty of Animal Science, Universitas Brawijaya, is optimistic that the results of the 5th APIS will just be as successful as the 4th APIS in 2019. The theme of 5th APIS was ""Developing Modern Livestock Production in Tropical Countries"". The 5th APIS discussed matters related to strategies for developing modern livestock production in several tropical countries. The participants of 5th APIS, including keynote speakers and invited speakers, are from various countries (tropical and sub-tropical). These proceedings present the selected papers from the 5th APIS conference.